LEARNING PROCESS FOR COMPETENCIES OF VILLAGE HEALTH VOLUNTEERS 4.0, ROI-ET - Chomphuviset, Patchara (Primary Health Care Journal (Northeastern Edition), 2022)
This research and development of purposes were to study problems and needs, improve the learning process and to study effectiveness of learning process for competencies development of village health volunteers 4.0. The research was divided into three phases: the study of problems and needs, learning process development and study the effectiveness of learning process, 80 of samples consisted the village health volunteers who met inclusion criteria and exclusion criteria. The research instruments were a test of the ability to use digital technology, health literacy test and volunteer spirit and transformational leadership assessment. The data were analyzed using mean,. standard deviation and paired t-test were statistically significant at 95% Confidence interval. The results showed that: The problem condition and the need for overall performance improvement were at a high level. The most use of digital technology in particular, the ability to use the Smart VHV application and use the application for health screening and assessment. The learning process consisted of1) situation analysis 2) learning process design 3) Implementation, and 4) feedback assessment, and after intervention, it was found that village health volunteers had average scores for their ability to use digital technology, more than before intervention (p<.001), with a mean score more than 4.97 (95%CI; 4.97, 4.58); mean difference a health literacy score more than before intervention (p<.001), with a mean score of health literacy morer than 4.97 (95%CI; 3.8, 6.13) and a mean volunteer spirit and transformational leadership score. statistically significantly more than before intervention (p<.001), with a score more of 1.78 (95%CI; 1.54, 2.01).